Enabling green product design with TRIZ - Tai, Marcus Jia En (2012)
With increasing pressure placed on companies to produce more environmentally friendly products, the need to innovate and solve problems quickly and consistently has never been more paramount to a company’s ability to succeed. The Theory of Inventive Problem Solving (TRIZ) offers users a scientific approach to problem solving, which eliminates the instinctive behaviour of guessing and randomly generating ideas to solve a problem. By systematically identifying the fundamental contradictions in the problem, users will be pointed in a general direction in order to find a solution. To fine-tune this design method for green product design, a new problem solving model was developed, and with the help of the Trisolver software, a case study on increasing the efficiency of vehicles in an urban driving environment was carried out. Using TRIZ, the author was able to find a solution to the immediate problem, and also found an application for this improvement in hybrid vehicles in general. It was also found that the bridging nature of TRIZ allowed it to be used with many other existing design methods, but the author also noted that the choice of which of these methods to utilise in the design process depended upon may factors, such as the users’ preferences and the topic of interest. Recommendations for further works were also proposed, and the conclusion was made based on the challenges encountered during the case study that TRIZ is indeed a powerful tool for green engineering product design.